Play their hearts out : a coach, his star recruit, and the youth basketball machine - Dohrmann, George. (Ballantine Books, 2010)
Pulitzer Prize-winning journalist George Dohrmann's remarkable debut offers an up-close and unforgettable narrative that reveals the gritty reality hiding behind the romanticized hoop dreams of America's basketball prodigies.